Resistance of young gelatinase B–deficient mice to experimental autoimmune encephalomyelitis and necrotizing tail lesions - Dubois, Bénédicte (American Society for Clinical Investigation, 1999)
Regulated expression of matrix metalloproteinases (MMPs) and their inhibitors (TIMPs) plays a role in various physiological processes. To determine in vivo how unbalanced expression of these factors can promote or affect the course of pathologies, we knocked out the mouse gelatinase B gene by replacing the catalytic and zinc-binding domains with an antisense-oriented neomycin resistance gene. Adult gelatinase B–deficient mice and wild-type controls could be induced to develop experimental autoimmune encephalomyelitis (EAE) with similar scores for neurologic disease, blood-brain barrier permeability, and central nervous system histopathology. However, whereas diseased control animals showed necrotizing tail lesions with hyperplasia of osteocartilaginous tissue, adult gelatinase B–deficient mice were resistant to this tail pathology. Gelatinase B–deficient mice younger than 4 weeks of age were significantly less susceptible to the development of EAE than were age matched controls and, even as they aged, they remained resistant to tail lesions. These data illustrate that gelatinase B expression plays a role in the development of the immune system and that, in ontogenesis, the propensity to develop autoimmunity is altered by the absence of this MMP. J. Clin. Invest. 104:1507–1515 (1999).